2019
DOI: 10.5194/acp-19-1571-2019
|View full text |Cite
|
Sign up to set email alerts
|

Free tropospheric aerosols at the Mt. Bachelor Observatory: more oxidized and higher sulfate content compared to boundary layer aerosols

Abstract: Abstract. Understanding the properties and life cycle processes of aerosol particles in regional air masses is crucial for constraining the climate impacts of aerosols on a global scale. In this study, characteristics of aerosols in the boundary layer (BL) and free troposphere (FT) of a remote continental region in the western US were studied using a high-resolution time-of-flight aerosol mass spectrometer (HR-AMS) deployed at the Mount Bachelor Observatory (MBO; 2763 m a.s.l.) in central Oregon in summer 2013… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 93 publications
11
30
0
Order By: Relevance
“…For many of these sites, ammonia denuders are used to minimize biases of ammonium on filters (e.g., Baltensperger et al, 2003). Data from remote highaltitude locations have indicated that the ammonium balance is less than 1 (Cozic et al, 2008;Sun et al, 2009;Freney et al, 2016;Zhou et al, 2019), similar to the observations from the AMS shown in Fig. 3.…”
Section: Impacts Of Ammonia Uptake On Acidic Filterssupporting
confidence: 79%
“…For many of these sites, ammonia denuders are used to minimize biases of ammonium on filters (e.g., Baltensperger et al, 2003). Data from remote highaltitude locations have indicated that the ammonium balance is less than 1 (Cozic et al, 2008;Sun et al, 2009;Freney et al, 2016;Zhou et al, 2019), similar to the observations from the AMS shown in Fig. 3.…”
Section: Impacts Of Ammonia Uptake On Acidic Filterssupporting
confidence: 79%
“…For many of these sites, ammonia denuders are used to minimize biases of ammonium on filters (e.g, (Baltensperger et al, 2003) ). Data from remote, high altitude locations have indicated that the ammonium balance is less than one (Cozic et al, 2008;Sun et al, 2009;Freney et al, 2016;Zhou et al, 2019) , similar to the observations from the AMS shown in Fig. 3 .…”
Section: Impacts Of Ammonia Uptake On Acidic Filterssupporting
confidence: 77%
“…The present results are consistent with those reported by Decarlo et al (2008) 11 , who observed elevated sulfate at the higher altitudes above MC. Similar studies of aerosol chemical composition conducted at other high-altitude sites in different parts of the world (in the absence of BB emissions) reveal that aerosols in the FT contain a high fraction of sulfates 11,43,44 .…”
Section: Elemental Compositionsupporting
confidence: 59%